Kajian Belis Ditinjau dari Aspek Sosial Budaya di Desa Marapokot, Kecamatan Aesesa, Kabupaten Nagekeo (Studi Kasus terhadap Hamil di Luar Nikah) - Yohthres Siga, Maria Eugenia; Nuwa, Gisela; Aswim, Danar (Universitas Syiah Kuala, 2025)
This study aims to determine the socio-cultural views of Marapokot Village, Aesesa District, Nagekeo Regency regarding belis and to determine the differences between belis for women who are pregnant outside marriage and women who are proposed to before marriage. The research method used is a qualitative descriptive method, primary data sources are: traditional leaders, community leaders and the person concerned, and secondary data sources are: books, journals, and articles. Data collection techniques used in this study are observation, interviews, and documentation. Data analysis techniques by collecting data, reducing data, presenting data and finally drawing conclusions. The results of the study show that the socio-cultural views of the Marapokot community regarding belis are considered as social identity and construction, a symbol of honor and family ties, maintaining the tradition and cultural identity of belis, and as a form of responsibility for men to protect women and children. In addition, there are differences in belis for women who are pregnant out of wedlock and women who are proposed to before marriage.